ANALISIS PROSEDUR PELAKSANAAN PADA PEKERJAAN DI RUANG TERBATAS (CONFINED SPACES) PADA PERBAIKAN TANGKI CPO DI PT. TUNGGAL PERKASA PLANTATIONS AIR MOLEK - LPPM Al-Insyirah (STIKes Al-Insyirah Pekanbaru, 2016)
The implementation of the assessment and risk control on the job in a limited space tank repair CPO in PT. Tunggal Perkasa Plantations Air Molek,good indispensable in which the object is to avoid of work accident and disease caused by work besides that manpower employment was asset for the company. As for this study aims to be able to analyze the potential danger confined spaces works on improving CPO tank in PT. Tunggal Perkasa plantations Air Molek 2015. Research conducted at the PT. Tunggal Perkasa Plantations Air Molek, research time 1 month from April-May 2015 using a qualitative design. The main subject of this research totaled 4 people consists of the head of the factory, Assistant SHE, krani ADM, and CPO operator. Engineering data collection using in-depth interviews, observation and document searches. Obtained that the implementation of the assessment and control of risks of work space is limited to the repair of the tank has not been running (CPO) in accordance with the regulations, due to the lack of awareness of the company's management in cultivate K3 on workers as well as less effective supervision K3 company when supervising work related to confined spaces. In conclusion, all the variables on the assessment and control of risks of work space is limited yet implementation according to existing guidelines. Optimize the role SHE did in the company of problem identification and supervision while working to prevent the occurrence of accidents and occupational health disorders.